2010
DOI: 10.1038/hdy.2010.104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of sexual dimorphism in the threespine stickleback Gasterosteus aculeatus

Abstract: Sexual dimorphism (SD) in morphological, behavioural and physiological features is common, but the genetics of SD in the wild has seldom been studied in detail. We investigated the genetic basis of SD in morphological traits of threespine stickleback (Gasterosteus aculeatus) by conducting a large breeding experiment with fish from an ancestral marine population that acts as a source of morphological variation. We also examined the patterns of SD in a set of 38 wild populations from different habitats to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 70 publications
3
54
1
2
Order By: Relevance
“…Additional stream-resident populations were from the Beaver, Boot, Joe’s, McCreight, Pye, and Robert’s systems [43], and from the inlet stream to Misty Lake [39], [75], on Vancouver Island. These freshwater samples were complemented by collections of marine stickleback from two estuaries on the east coast of Vancouver Island (Cluxewe: 50°36′51″ N, 127°11′10″ W; Sayward [76]), from the Japan Sea and Pacific [77], from the Atlantic Coast in Norway [78], and from the coast of the White Sea in Russia [79]. All these additional samples were also collected during the reproductive season on breeding grounds.…”
Section: Methodsmentioning
confidence: 99%
“…Additional stream-resident populations were from the Beaver, Boot, Joe’s, McCreight, Pye, and Robert’s systems [43], and from the inlet stream to Misty Lake [39], [75], on Vancouver Island. These freshwater samples were complemented by collections of marine stickleback from two estuaries on the east coast of Vancouver Island (Cluxewe: 50°36′51″ N, 127°11′10″ W; Sayward [76]), from the Japan Sea and Pacific [77], from the Atlantic Coast in Norway [78], and from the coast of the White Sea in Russia [79]. All these additional samples were also collected during the reproductive season on breeding grounds.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, however, sex chromosomes are not the leader of sexual dimorphism, because quantitative genetic studies have observed discordance between sex chromosomes and phenotypic data [79]. Genetic architecture of threespine stickleback fish (Gasterosteus aculeatus) is very similar between males and females, but many traits show significant sexual difference, suggesting that genetic constraints for evolution of sex dimorphism might not be so severe and absolute as generally thought [80]. A great deal of data accumulation of the completely sequenced genomes, transcriptomes, and proteomics from model and farmed fishes provides a previous basis for us to explore the genetic and molecular mechanism of sex dimorphism [12].…”
Section: Genetic Basis Of Sexual Dimorphism In Fishmentioning
confidence: 99%
“…Sexual dimorphism in fish not only includes size dimorphism, shape dimorphism and color dimorphism, but also comprises sexual differences in physiology and behavior [43,44]. Long-term field surveys and aquaculture practices have observed significant size dimorphism between male and female individuals in more than 20 fish species.…”
Section: Sexual Dimorphism and Its Genetic Basis In Fish 21 Diversitmentioning
confidence: 99%
“…Stickleback are known to exhibit sexual dimorphism in body shape and trophic morphology (Caldecutt and Adams, 1998;Kitano et al, 2007;Aguirre et al, 2008;Aguirre and Akinpelu, 2010;Leinonen et al, 2011). Additionally, males exhibit sex-specific behaviors involving the trophic apparatus (Stanley and Wootton, 1986).…”
Section: Introductionmentioning
confidence: 99%